Pregnancy outcomes of antiphospholipid syndrome: In a low resource South Asian setting - Wijeyaratne, C.N.; Galappaththi, S.L.A.; Palipane, E.; Jayawardane, D.B.I.A.; Dodampahala, S.H.; Tudawe, M.N.; Gooneratne, L.V.; De Silva, R.; Ratnayake, D.; Seneviratne, S.L. (SAGE, 2016)
Problem: Antiphospholipid syndrome is associated with recurrent pregnancy loss, and specific treatment improves pregnancy outcome. Laboratory diagnosis is limited in South Asia. We assessed management outcomes of definite/probable antiphospholipid syndrome treated at a tertiary centre in Sri Lanka. Method: Descriptive cross-sectional study of pregnancy outcomes with heparin and aspirin therapy. Outcome measures: miscarriage, intrauterine death and live birth when compared to previous untreated pregnancies. Results: Of 646 gestations in 145 women, 146 (22.6%) received specific treatment. In the preceding pregnancies without specific treatment, the rates of miscarriage, late fetal loss, stillbirth and live birth were 60%, 26%, 8% and 7%, respectively. Following specific treatment with low-dose aspirin ± low-molecular weight heparin in 146 pregnancies (145 women), the rates of miscarriage, late fetal loss, stillbirth and live birth were 14%, 10%, 3% and 74%, respectively. Mean birth weight was 2.54 ± 0.62 kg, preterm births complicated 32 (29.6%) with a mean gestational age at delivery 33.7 ± 2.6 weeks, with three neonatal deaths. Maternal complications were: pre-eclampsia 16 (10.9%), gestational diabetes 28 (19.2%), antepartum haemorrhage in 1 patient. Only 73/145 (50.3%) women had laboratory confirmation of antiphospholipid syndrome, while others were treated empirically. Live births in diagnosed vs. empiric treatment – 80.8% vs. 67.1%. Conclusion: Pregnant women with clinical antiphospholipid syndrome when treated with low-dose aspirin and heparin, the live birth rate of 7% in the previous pregnancy resulted in live births of 74% in a resource limited South Asian setting.
Keywords: Heparin; Sri Lanka; low-dose aspirin; recurrent pregnancy loss